Photoinitiated polymerization of ethyl cyanoacrylate by phosphonium salts - Önen, A; Arsu, N; Yagci, Y (WILEY-V C H VERLAG GMBH, 1999)
The photoinitiated polymerization of ethyl cyanoacrylate (ECA) by benzyl triphenylphosphonium hexafluoroantimonate (BP+) and (anthracen-9-ylmethyl)triphenylphosphonium hexafluoroantimonate (MAP(+)) was studied. Zwitterionic and free radical mechanisms which involved homolytic and heterolytic decomposition of the phosphonium salts are discussed. The anthracene-sensitized photopolymerization of ECA was also demonstrated.
Keywords: PHOTOSENSITIZED CATIONIC POLYMERIZATION; METHYL-METHACRYLATE; PYRIDINIUM SALTS; BENZYL; Polymer Science